Multimodality Imaging Evaluation of Primary Right Atrial Paraganglioma: A Case Report and Literature Review - Huang, Wen-peng; Gao, Ge; Chen, Zhao; Qiu, Yong-kang; Gao, Jian-bo; Kang, Lei (Frontiers in Medicine, 2022)
Background Cardiac paraganglioma (CPGL) accounts for 1–3% of cardiac tumors and is usually benign. In total, 35–50% of CPGL lesions secrete catecholamines, causing hypertension, excessive sweating, palpitations, headache, and other symptoms. Preoperative imaging evaluation is important to determine the location of the cardiac mass, its blood supply vessels, and the relationship with surrounding structures. Multimodal imaging techniques combine with morphological and functional information to provide powerful methods for preoperative diagnosis and lesion localization. Furthermore, they can assist to reduce the incidence of intraoperative and postoperative complications and improve patient prognosis. Case Report A 67-year-old woman suffered from paroxysmal palpitations with a heart rate of 110 beats per minute 1 month ago. Urine catecholamine and methoxyepinephrine levels were significantly increased. The patient had a 5-year history of hypertension with a maximum blood pressure of 160/100 mmHg. Computed tomography (CT) examination found a soft tissue mass in the right atrium with heterogeneous and significant enhancement, whose blood supply was from the left ileal branch artery. The patient then underwent cardiac magnetic resonance (CMR). The lesion showed inhomogeneous iso signals on the T1-weighted image (T1WI), slightly high signals on the T2 fat-suppression image, inhomogeneous high signals on the diffusion-weighted imaging (DWI), and apparent diffusion coefficient (ADC) images. The mass exhibited heterogeneous and significant enhancement on the first perfusion and delayed scans after intravenous contrast injection. However, abnormal signals were surprisingly found in the patient’s right lung, and the possibility of metastatic lesions could not be excluded. The patient underwent F-18 fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG PET/CT) to rule out metastatic lesions. A fluorodeoxyglucose (FDG)-avid soft tissue mass was shown in the right atrium, with the maximum standardized uptake value (SUVmax) at about 15.2, as well as a pathological intake of brown fat throughout the body. Combined with clinical symptoms, CPGL was considered without significant sign of metastasis in 18F-FDG PET/CT. Finally, the patient underwent surgical resection and the post-operative pathology confirmed a CPGL. Conclusion The combination of 18F-FDG PET/CT with the CMR containing different image acquisition sequences provides a powerful aid for preoperative non-invasive diagnosis, localization, and staging of CPGL, which helps to reduce intraoperative and postoperative complications and improve patient prognosis.